GEOMECHANICAL AND HYDRAULIC FRACTURING ANALYSIS OF UBADARI FIELD, BINTUNI BASIN - Naufal Yunan, Muhammad
Ubadari Field is one of BP Indonesia’s gas field which is located in Bintuni Bay, West Papua. The main reservoir of Ubadari Field is sandstone on Waripi Formation and Roabiba Interval. There is overpressure phenomenon that affected the in-situ stresses value. Research is conducted by processing log data to obtain vertical stress value using density log, minimum horizontal stress value by using leak off test and empirical equation, and maximum horizontal stress by empirical equation. Image log is used to determine the direction of the horizontal stresses and akakier the model is completed, hydraulic fracturing analysis is performed based on PKN model in the pay interval and generate fracture pressure, width, and fracture height grown value. From the modelling which have been done, the result shows that Ubadari Field is undergoing strike-slip faulting regime, with the direction of maximum horizontal stress is at Northeast-Southwest. Increase in pore pressure value lead to shikakiing on horizontal stresses gradient. The hydraulic fracturing analysis yield that the fracture will propagate in vertical direction and formed at 0.46 MPa injecting pressure value and formed a fracture width about 0.16 mm.the fracture will propagate up into 30 ft above the pay zone and 60 ft below the pay zone. There is no pre-existing fracture reactivation during the injection process.